2013
DOI: 10.3109/1547691x.2013.809175
|View full text |Cite
|
Sign up to set email alerts
|

Serrumab: A novel human single chain-fragment antibody with multiple scorpion toxin-neutralizing capacities

Abstract: In Brazil, scorpion envenomation is an important public health problem. The yellow scorpion, Tityus serrulatus (Ts), is considered the most dangerous species in the country, being responsible for the most severe clinical cases of envenomation. Currently, the administration of serum produced in horses is recognized and used as a treatment for accidents with scorpions. However, horse herds' maintenance is costly and the antibodies are heterologous, which can cause anaphylaxis and Serum Sickness. In the present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Two research groups independently isolated scFvs that recognize toxins from the Tityus serrulatus venom, and in both cases, this was carried out after panning human naive libraries [70,71,72]. By opting for this strategy, researchers avoided long-term animal immunization protocols and focused on the expected lack of immunogenicity of human-derived molecules.…”
Section: Preclinical Evaluation Of Recombinant Antibodies For the mentioning
confidence: 99%
“…Two research groups independently isolated scFvs that recognize toxins from the Tityus serrulatus venom, and in both cases, this was carried out after panning human naive libraries [70,71,72]. By opting for this strategy, researchers avoided long-term animal immunization protocols and focused on the expected lack of immunogenicity of human-derived molecules.…”
Section: Preclinical Evaluation Of Recombinant Antibodies For the mentioning
confidence: 99%
“…One obtained scFv was investigated for its neutralizing abilities both through in vitro biochemical assays and in a murine model, where it showed partially neutralizing effects. In a later study of the same scFv, it was additionally shown that the scFv could neutralize the effects of similar β-neurotoxins from other scorpion genera [ 58 ].…”
Section: Selected Examples Of the Use Of Antibody Phage Display Sementioning
confidence: 99%
“…Immersion in tricaine solution (1 g/L) was the anesthetic method used to induce anesthesia. The frog procedure was as previously used [7,21,24,31].…”
Section: Na + and K + Channels Expressionmentioning
confidence: 99%